The Stability of the International Monetary System - Scammell W.M (Rowman And Littlefield Education, 1987)
List of Tables, Preface, Introduction, The Necessities of the System, A Little History, International Money, What Sort of Exchange Rates?, Theoretical Approaches to Adjustment, The Role and Mechanism of Capital Flows, Control of the International Monetary System, Conclusion, Index.